Jawabanmu

2014-04-21T20:53:32+07:00
x² - 3x - 2 = 0, maka a = 1, b= - 3, dan c = -2
(3x1+1) + (3x2+1).
= 3X1 + 3X2 + 2
                           = 3(X1 + X2) + 2
                           = 3(-b/a) + 2
                           = 3(3/1) + 2
                           = 11
(3x1+1)(3x2+1).    = 9x1x2 + 3(x1 + x2) + 1
                           = 9(c/a) + 3(-b/a) + 1
                           = 9 (-2/1) + 9 + 1
                           = -8
Pers. Kwd baru :     x² - ((3x1+1)+(3x2+1))x + (3x1+1)(3x2+1) = 0  
                             x² - 11x - 8 = 0